Pengaruh Alat Peraga Kotak Belajar Ajaib (Kobela) Terhadap Hasil Belajar Matematika Siswa SD Negeri 1505 Pasir Julu Kab. Padang Lawas - Lili Khodniar Hasibuan; Riris Nurkholidah Rambe; Sahkholid Nasution (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The aims of this study were, 1) to find out the results of students learning mathematics learning using the magic learning box (Kobela) teaching aid, 2) the magical use of learning teaching aids (Kobela), 3) the effect of the magic learning box (Kobela) teaching aids for the mathematics learning outcomes of class IV students at SD Negeri 1505 Pasir Julu District. Sosa Julu, Kab. Padang Lawas. The research methodology uses a quantitative approach with the Quasy Experiment type in the form of Nonequivalent Control Group Design. This research was conducted at SD Negeri 1505 Pasir Julu Kec. Sosa Julu District. Padang Lawas. The population and sample of this study were all four class students at SD Negeri 1505 Pasir Julu consisting of 2 classes totaling 49 students and the test instrument used is in the form of multiple choice. This type of data analysis was carried out by analyzing the Paired Sample T-test. The results of this study indicate 1) Student learning outcomes using simple visual aids obtain an average pretest score of 31.42 and 73.33 posttest. 2) student learning outcomes using the magic learning box (Kobela) visual aids obtained an average pretest score of 35.89 and 85.53 posttest. 3) this has the effect of the magic learning box (Kobela) teaching aid on student learning outcomes. The results of learning mathematics at SD Negeri 1505 Pasir Julu are proven by the results of the Paired Sample T Test with a Sig value of 0.00 <0.05 so that